Epic cosplay costumes : a step-by-step guide to making and sewing your own costume designs - Good, Kristie (Fons & Porter, 2016)
Presented in a kitschy, comic-book style, Epic Cosplay Costumes combines fantabulous illustrations with all the how-to information you need for creating your own cosplay designs. Award-winning artist Kristie Good (aka Karmada) shares techniques for making must-have pieces to mix and match into original costumes--from hand-sewn garments to armor made with Worbla and EVA foam. In addition to her step-by-step instructions for pulling together attention-grabbing designs, she shares expert advice for making the most of conventions, striking a pose, and strutting your stuff at costume competitions. Whether you're a hero, heroine, villain, or sidekick, Kristie gives you the power to create the most talked-about designs with Epic Cosplay Costumes!